PENGARUH ABILITY DAN IKLIM ORGANISASI TERHADAP PERILAKU INOVATIF DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (Studi pada Tenaga Pranata Laboratorium Pendidikan (PLP) di Politeknik Negeri Malang) - Riani, Candra; Astuti, Endang Siti; Utami, Hamidah Nayati (Profit: Jurnal Adminsitrasi Bisnis, 2017)
This study examines the influence of ability and organizational climate and organizational innovative behaviour towards citizenship behavior. Free variables in the peneltian this is the abilty of the variable (X 1) and organizational climate variables (X2) while the variable is bound in this research are innovative behaviour (Y1), organizational citizenship behavior (Y2). The five hypotheses formulated related research objectives. This research uses a quantitative approach to data and research is a kind of eksplanatori. Data collection is done using questionnaires, from 26 questionnaires presented and everything back.Â  To test the hypothesis testing done path analysis using Least Square SmartPartial. Before the test is done hypothesis testing test validity and reliability. The results of this research show that abilty influential significantly to organizational citizenship behavior in addition to this ability also has significantly to innovative behavior. While it was found that the Organization's influential climate not significantly to innovative behavior and also organizational citizenship behavior. As for innovative behaviour also has not significantly to organizational citizenship behavior.Â